2005
DOI: 10.1373/clinchem.2004.046474
|View full text |Cite
|
Sign up to set email alerts
|

Technology for Automated, Rapid, and Quantitative PCR or Reverse Transcription-PCR Clinical Testing

Abstract: Background: PCR-based assays can improve clinical care, but they remain technically demanding and labor-intensive. We describe a new instrument, the GeneXpert ® , that performs automated nucleic acid isolation, reverse transcription, and fluorescence-based quantitative PCR in ϳ35 min. Methods: Yield and integrity of RNA isolated on the GeneXpert were compared with Qiagen-based extraction for parallel samples (5-m frozen tissue sections). The reproducibility of automated RNA isolation, reverse transcription, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
69
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 24 publications
0
69
0
2
Order By: Relevance
“…This selfcontained automated instrument integrates microfluidic sample preparation with RT-PCR-based, real-time fluorescent signal detection. 13 Virtually all of the reagents used for both the RNA preparation and the subsequent RT-PCR and PCR steps are lyophilized into a disposable multichambered cartridge, potentially decreasing both reagent-and pipette-related bias. The sample is transferred through the chambers during the extraction process by the pumping action of a central piston; subsequently, the purified RNA reaches the detection chamber where the reverse transcription, the multiplexed amplification steps, and the fluorescent signal detection take place.…”
mentioning
confidence: 99%
“…This selfcontained automated instrument integrates microfluidic sample preparation with RT-PCR-based, real-time fluorescent signal detection. 13 Virtually all of the reagents used for both the RNA preparation and the subsequent RT-PCR and PCR steps are lyophilized into a disposable multichambered cartridge, potentially decreasing both reagent-and pipette-related bias. The sample is transferred through the chambers during the extraction process by the pumping action of a central piston; subsequently, the purified RNA reaches the detection chamber where the reverse transcription, the multiplexed amplification steps, and the fluorescent signal detection take place.…”
mentioning
confidence: 99%
“…It can now be concluded that real-time qRT -PCR assay for biomarker mRNA, particularly when used with a specific probe and RNA copy standard, is a superior method for micrometastases detection because it is objective, highly sensitive and quantitative, and has a very wide measuring range (Godfrey et al, 2001;Ho et al, 2004;Ö berg et al, 2004). Moreover, this technology lends itself to automation and rapid test performance suitable for a clinical setting (Raja et al, 2005).…”
mentioning
confidence: 99%
“…The system will be running on the GeneXpert platform (Cepheid, Sunnyvale, CA) by using disposable cartridge that contains a previously-determined reagent. 13 GeneXpert provided as a simple method that works automatically, take two hours, and is not require an expert to perform this examination. Several reports described the success of GeneXpert on detecting every pulmonary TB cases among all suspects, including more than 90% of suspects with negative results in acid fast staining examination.…”
Section: Introductionmentioning
confidence: 99%